Механизмы формирования неологизмов в прессе современного французского языка - Афанасьева, О.В.; Норец, Т.М. (Культура народов Причерноморья, 2014)
Данная статья посвящена механизмам формирования неологизмов в прессе. В работе
рассматриваются теоретическое обоснование и принципы исследования неологизмов в
словообразовательной системе французского языка, типологическая классификация неологизмов, пути
возникновения и функции неологизмов. Были выявлены и подробно описаны словообразовательные
модели по которым возникают неологизмы в газетном тексте во французском языке, определена роль
новой лексики как вербальной составляющей в создании прагматического потенциала газетного текста
во французском языке, а также смысловые преобразования в семантических неологизмах в языке
прессы. Дана стаття присвячена механізмам формування неологізмів у пресі. У роботі
розглядаються теоретичне обгрунтування і принципи дослідження неологізмів у словотворчій системі
французької мови, типологічна класифікація неологізмів, шляхи виникнення і функції неологізмів. Були
виявлені і детально описані словотворчі моделі за якими виникають неологізми в газетному тексті у
французькій мові, визначена роль нової лексики як вербальної складової в створенні прагматичного
потенціалу газетного тексту у французькій мові, а також смислові перетворення в семантичних
неологізмах в мові преси. This article deals with the mechanisms of formation of neologisms in the press. The paper deals with
the theoretical basis and principles of research neologisms in French word-formative system, the analysis of the
standard models for the formation of neologisms in the French language, typological classification of
neologisms, the origins of features and neologisms themselves. Have been identified and described in detail
derivational models that give rise to neologisms in the newspaper text in the French language. Connotative
meanings set those morphemes which they acquire by participating in the formation of new vocabulary.
Identified the role of vocabulary as a verbal component in the creation of pragmatic capacity of newspaper text
in the French language. Were defined semantic transformation in semantic neologisms in language press. The
theoretical framework for the development of this problem makes it possible to identify the main ways of
enriching vocabulary of the language and hence reveal the trends in the development of this vocabulary, that is
mostly used in Russian and French at the present stage of their development.